Managing Service Quality and Customer Relationship Management to Increase Customer Satisfaction and Customer Retention - Prakoso, Budi (The International Journal of Business Review (The Jobs Review), 2023)
Customer retention (Customer Retention/CR) is very important for a company, with customer retention the company can survive and continue to grow. Many policies have been made by CEOs of multinational companies as well as research conducted by researchers to find out what factors are effective and have an impact on customer retention. This study aims to determine the relationship between the variables Service Quality, Customer Relationship Management, Customer Satisfaction, and Customer Retention. The analysis is based on 217 respondents who are customers who have used services at the company through a survey questionnaire. The measurement model for the analysis of the research hypothesis uses the Partial Least Square (PLS) procedure. The results showed that the CRM variable had a positive effect on the SQ variable, the SQ variable had a positive effect on the CS variable, the CRM variable had a positive effect on the CS variable, the SQ variable had a positive effect on the CR variable, the CRM variable had a positive effect on the CR variable, the CS variable had a positive effect on the CR variable CR. The advice that can be given is the need to maintain and improve the quality of service and customer relations, because it will give the company customer satisfaction which has an impact on customer retention. Companies also need to consider the feedback obtained from the customer relationship system to improve service quality and customer relations themselves.